2014
DOI: 10.1155/2014/825936
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ocular Pseudoexfoliation and Sensorineural Hearing Loss

Abstract: Background. Our study aimed to investigate an association between ocular pseudoexfoliation (PXF) and sensorineural hearing loss (SNHL) and to compare them with age and sex matched controls without pseudoexfoliation. Method. This was a case-control study of 123 patients which included 68 cases with PXF (at least one eye) and 55 controls without pseudoexfoliation. Pure-tone audiometry (PTA) was done for these patients at sound frequencies taken as important for speech comprehension, that is, 250 Hertz (Hz), 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…; Singham et al. ). It has been suggested that in XFS, the cochlea might be affected through exfoliation microfibrillar deposits that lead to dysfunction of the mechanoreceptors in the inner ear (organ of Corti) and thus impact on hearing (Cahill et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Singham et al. ). It has been suggested that in XFS, the cochlea might be affected through exfoliation microfibrillar deposits that lead to dysfunction of the mechanoreceptors in the inner ear (organ of Corti) and thus impact on hearing (Cahill et al.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
“…Researchers have noted the association between PEX and some neurological diseases. Singham et al suggested that the accumulation of pseudoexfoliation material in sensorineural cells could explain the association between PEX and hearing loss [26]. Zojaji et al also showed a strong association between PEX and sensorineural hearing loss [27].…”
Section: Discussionmentioning
confidence: 99%